2002
DOI: 10.4049/jimmunol.169.1.366
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of Type I IFN Genes in Human Dendritic Cells Infected withMycobacterium tuberculosis

Abstract: Type I IFN regulates different aspects of the immune response, inducing a cell-mediated immunity. We have recently shown that the infection of dendritic cells (DC) with Mycobacterium tuberculosis (Mtb) induces IFN-α. In this work we have monitored a rapid induction of IFN-β followed by the delayed production of the IFN-α1 and/or -α13 subtypes. The Mtb infection rapidly activates the NF-κB complex and stimulates the phosphorylation of IFN regulatory factor (IRF)-3, events known to induce IFN-β expression in vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 70 publications
(64 reference statements)
3
97
3
Order By: Relevance
“…The next question was to elucidate if STAT-1 tyrosine phosphorylation resulted from a direct effect of NiSO 4 on Jak activity or through the synthesis of an intermediate factor. Indeed, type I IFNs are well-known inducers of STAT-1 tyrosine phosphorylation in Mo-DCs (38). We found that NiSO 4 upregulated the ifn-b mRNA, but IFN-b was undetectable in the supernatants of Mo-DC treated for 24 h by NiSO 4 (data not shown).…”
Section: Nickel Induces the Expression Of Irf-1 Which Contributes To mentioning
confidence: 59%
“…The next question was to elucidate if STAT-1 tyrosine phosphorylation resulted from a direct effect of NiSO 4 on Jak activity or through the synthesis of an intermediate factor. Indeed, type I IFNs are well-known inducers of STAT-1 tyrosine phosphorylation in Mo-DCs (38). We found that NiSO 4 upregulated the ifn-b mRNA, but IFN-b was undetectable in the supernatants of Mo-DC treated for 24 h by NiSO 4 (data not shown).…”
Section: Nickel Induces the Expression Of Irf-1 Which Contributes To mentioning
confidence: 59%
“…31 DCs have also been shown to produce type I interferons in response to micro-organisms as well as in response to viral infection or following interaction with T cells. [32][33][34][35][36][37][38] In mice, enhanced IL-12 or IL-10 production by DCs requires two signals, one from the encounter with the pathogen and the second from the interaction with T cells, [39][40][41] suggesting that the role of the pathogen in mice is to 'sensitize' DCs such that they can be fully activated following encounter with T cells. Similar studies in human-derived DC have not been reported.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…In line with these findings, Jagannath and collaborators showed that in a mouse model the stimulation of autophagy by rapamycin enhanced the capacity of DC to present mycobacterial antigens into the MHC class II complex. 13 Given the critical role played by DC in the regulation of the immune response against Mtb, [22][23][24] we sought to investigate the modulation of the autophagic process in human primary DC infected by Mtb and the vaccine strain BCG. We show that Mtb, but not BCG, impairs the late steps of autophagy and a functional ESX-1 secretion system is required for this inhibition.…”
Section: Mtb and Bcg Have Different Impacts On The Autophagic Processmentioning
confidence: 99%